Thermal comfort of female buffaloes in a silvipasture system in the eastern Amazon - da Silva, Jamile Andréa Rodrigues; de Araújo, Airton Alencar; Lourenço Júnior, José de Brito; dos Santos, Núbia de Fátima Alves; Garcia, Alexandre Rossetto; Nahúm, Benjamim de Souza (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effects of a silvipasture system on the thermal comfort of 20 female buffaloes, from which 10 raised in under nonshaded paddocks (SS) and 10 in paddocks shaded by Racosperma mangium (CS), in Belém county, PA, Brazil. All animals were fed in pastures with Urochloa humidicola, and had free access to drinking water and mineral salt. Every three days, measurements were made for air temperature (TA), relative humidity (UR), black globe temperature (TGN), rectal temperature (TR), respiratory rate (FR), heart rate (FC), and body surface temperature (TSC), in the morning (7 AM) and in the afternoon (1 PM). The values of TR, TSC, RR and FR, mainly for the SS group, were higher in the afternoon. The TR, TSC and FR showed a significant and positive correlation with TA and the temperature and humidity index (ITGU), and a negative correlation with UR. These correlations were higher for the less rainy period. The FR showed significant and positive correlations with TA and ITGU, during both the most and the less rainy seasons, and negative correlations with UR only in the rainy season. The forestation of pasture areas is efficient to increase the thermal comfort for Murrah females, especially in the afternoon.